The Effect of CEO Ethnicity, Ownership Concentration, and Audit Committee on Audit Report Lag - Umi Kalsum; Rika Henda Safitri; Dirta Pratama Atiyatna; Audrey Audrey (Journal of Governance and Accountability Studies, 2025)
Purpose: This study examines several factors that may affect audit report lag, including CEO ethnicity, ownership concentration, and the number of audit committee meetings among LQ 45 companies in Indonesia from 2019 to 2022. Methods: This study employed a quantitative descriptive method to examine the relationships between variables, including the partial effects. SPSS was used as the statistical analysis tool to conduct descriptive statistics, assess assumption classifications, perform regression analysis of the research model, and test hypotheses using partial tests and the coefficient of determination. Results: The results of this study indicate that the CEO ethnicity and audit committee variables do not significantly affect audit report lag. However, the audit committee variable partially has a significant influence on audit report lag. Conclusion: CEO ethnicity does not significantly affect audit report lag. In contrast, ownership concentration significantly affects audit report lags. Furthermore, the audit committee variable does not significantly affect the audit report lag. Limitation: Audit Report Lag can reduce the usefulness and reliability of financial reports for users. There is a lack of references to these variables, especially the rarely studied ethnic variables. This study contributes to the literature by examining the relationship between the ethnicity and race of CEOs at LQ 45 companies as the research subject. Contributions: This study contributes to the audit literature by providing empirical evidence of the influence of CEO ethnicity, ownership concentration, and audit committee activities on audit report lag, specifically within LQ45 companies in Indonesia, highlighting the unique role of ethnic diversity in corporate governance contexts.